Pyroptosis in the Retinal Neurovascular Unit: New Insights Into Diabetic Retinopathy - Meng, Chunren; Gu, Chufeng; He, Shuai; Su, Tong; Lhamo, Thashi; Draga, Deji; Qiu, Qinghua (Frontiers in Immunology, 2021)
Diabetic retinopathy (DR) is prevalent among people with long-term diabetes mellitus (DM) and remains the leading cause of visual impairment in working-aged people. DR is related to chronic low-level inflammatory reactions. Pyroptosis is an emerging type of inflammatory cell death mediated by gasdermin D (GSDMD), NOD-like receptors and inflammatory caspases that promotes interleukin-1β (IL-1β) and IL-18 release. In addition, the retinal neurovascular unit (NVU) is the functional basis of the retina. Recent studies have shown that pyroptosis may participate in the destruction of the retinal NVU cells in the simulated hyperglycemic DR environments. In this review, we will clarify the importance of pyroptosis in the retinal NVU during the development of DR.